2020
DOI: 10.1111/acel.13206
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutation exacerbates female reproductive aging via impairment of the NADH/NAD+ redox

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 72 publications
(87 reference statements)
5
59
0
Order By: Relevance
“…Ovarian aging is related to reduced oocyte mtDNA content, and studies have shown that the mtDNA copy number per oocyte of young women is significantly higher than that of aged women or those of the same age with DOR ( Pasquariello et al, 2019 ). In addition, the accumulation of female mouse germline mtDNA mutations exacerbates ovarian aging and reduces lifespan ( Ross et al, 2014 ; Yang et al, 2020 ). Evidence for this is that the mitochondrial content of GCs and oocytes was significantly decreased in a mouse model of fragile X primary ovarian insufficiency ( Conca Dioguardi et al, 2016 ).…”
Section: Effects Of Oxidative Stress On Mitochondria In the Ovariesmentioning
confidence: 99%
“…Ovarian aging is related to reduced oocyte mtDNA content, and studies have shown that the mtDNA copy number per oocyte of young women is significantly higher than that of aged women or those of the same age with DOR ( Pasquariello et al, 2019 ). In addition, the accumulation of female mouse germline mtDNA mutations exacerbates ovarian aging and reduces lifespan ( Ross et al, 2014 ; Yang et al, 2020 ). Evidence for this is that the mitochondrial content of GCs and oocytes was significantly decreased in a mouse model of fragile X primary ovarian insufficiency ( Conca Dioguardi et al, 2016 ).…”
Section: Effects Of Oxidative Stress On Mitochondria In the Ovariesmentioning
confidence: 99%
“…Consistent with this idea, enriched GO terms for downregulated genes included oxidoreductase activity, cellular respiration, and cellular response to stress ( S13 and S14 Figs). These pathways have been recently shown to be important for the generation of high quality oocytes in mammals [ 59 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the cell type, it is well known that mitochondrial DNA is more sensitive to mutation than nuclear DNA and that aging is an important risk factor. In mammalian oocytes, mitochondrial DNA mutations increase with age and are inversely correlated with oocyte quality [97][98][99]. In mice, oocyte mitochondrial DNA content increases during in vivo oogenesis without difference according to mice age [100].…”
Section: Discussionmentioning
confidence: 99%